Giant cell tumours in mandible and spine: a rare complication of Paget's disease of bone. Issue 12 (December 1992) - Bhambhani, M; Lamberty, B G; Clements, M R; Skingle, S J; Crisp, A J
Abstract : The case of a man who was diagnosed as having polyostotic Paget's disease at the age of 52 years is described. He developed a rare neoplastic complication of Paget's disease–a giant cell tumour in his mandible, which was excised. Nine years after the diagnosis of this tumour he developed a new giant cell tumour arising from the L3 vertebral body. He was born in Avellino in Italy, from where five other cases of giant cell tumours arising from Pagetic bone disease have been reported. No family relationship between our patient and the other cases was established. His Paget's disease was particularly aggressive and resistant to treatment with two single high dose infusions of pamidronate almost two years apart.